Bone mineral density on conventional and digitized images under different parameters of digitization and storage - de Oliveira, Matheus Lima; Bóscolo, Frab Norberto; Tosoni, Guilherme Monteiro [UNESP] (My University, 2010)
Aim: To assess the bone mineral density on conventional and digitized images, comparing whether different parameters of digitization and storage change these values. Methods: Twenty radiographs were taken from five partially dentulous dry mandibles with an aluminum 7-mm stepwedge placed on the superior edge of the film. After processing, the films were digitized with a resolution of 600 and 2,400 d.p.i. and saved as TIFF and JPEG files. On every conventional and digitized image, circular regions of interest were selected for densitometry and radiographic contrast analysis. Results: Pearson's correlation coefficient showed a significant and strong mean gray values association between digitized and conventional images, differing from radiographic contrast that did not show a significant association. ANOVA did not reveal a statistically significant difference in bone density and radiographic contrast among the four digitized image groups, but the conventional image contrast was significantly lower. Conclusions: Bone mineral density did not differ in both conventional and digitized images. The parameters of image compression and resolution, tested in this study, did not change the results of densitometry and digitization process increased the radiographic contrast.
Keywords: Bone density; Densitometry; Dental radiography; Digital dental radiography